Risk Analysis of MSME and MSM Credit by Economic Sectors - Cundo Harimurti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyse the credit risk of the Micro, Small, Medium Enterprises and Micro Small Medium sector by economic sector during the Covid-19 Pandemic. Time series research data for the period 2011-2020 from Indonesian Banking Statistics With the secondary data analysis method, it is known that the average non-performing loan for MSMEs and MSM for a period of 10 years according to the wholesale and retail sector is IDR 14.062 trillion, Construction of IDR 3.244 trillion, Processing Industry of IDR 2.908 trillion, Agriculture, Hunting and Forestry of IDR 2.040 trillion, Real Estate, Rental Business, and Corporate Services are amounting to IDR 1.334 trillion, Transportation, Warehousing and Communication of IDR 1.145 trillion, Social, Cultural, Entertainment and Other Personal Services of IDR 1.089 trillion, Accommodation, Food and Beverage of IDR 904 billion, Mining and Quarrying of Rp. 431 billion, Financial Intermediaries IDR 303 billion, Fisheries of IDR 190 billion, Health Services and Social Activities of IDR 127 billion, Electricity, Gas, and Water of IDR 78 billion, Education Services of IDR 52 billion, Individual Services Serving Households of IDR 44 billion. One of the reasons for the increase in non-performing loans for MSMEs and MSMs is the weak economic activity resulting from the COVID-19 pandemic, which has triggered a decrease in credit demand and has pushed up non-performing loans due to the decline in the ability to pay from MSME and MKM actors.